Exports and Productivity in Germany - Joachim Wagner (Max Planck Institute of Economics, 2007)
Using unique recently released nationally representative high-quality longitudinal data at the plant level, this paper presents the first comprehensive evidence on the relationship between exports and productivity for Germany, a leading actor on the world market for manufactured goods. It applies and extends the now standard approach from the international literature to document that the positive productivity differential of exporters compared to non-exporters is statistically significant, and substantial, even when observed firm characteristics and unobserved firm specific effects are controlled for. For West German plants (but not for East German plants) some empirical evidence for self-selection of more productive firms into export markets is found. There is no evidence for the hypothesis that plants which start to export perform better in the three years after the start than their counterparts which do not start to sell their products on the world market. Results for West Germany support the hypothesis that the productivity differential between exporters and non-exporters is at least in part the result of a market driven selection process in which those export starters that have low productivity at starting time fail as a successful exporter in the years after the start, and only those that were more productive at starting time continue to export.
Keywords: F14; D21; 330; Exports; productivity; micro data; Germany; Exportindustrie; Verarbeitendes Gewerbe; Produktivität; Vergleich; Deutschland